2021
DOI: 10.2147/hiv.s336886
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Exercise for Older People Living with HIV: A Scoping Review

Abstract: Introduction: Improvements in physical, mental, and overall quality of life are well documented in younger HIV populations who exercise. Exercise guidelines exist for younger HIV populations, but none for older people living with HIV (OPLWH), especially 50 years of age and older. Our aim was to map the existing literature on the effects of exercise and physical activity prescriptions for OPLWH. Methods: We conducted a scoping review using the methodological framework proposed by the Joanna Briggs Institute. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 60 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Participants took part in a face-to-face, semi-structured interview [each approximately 60 min in length] between June and November 2021. There were sixteen [16] individuals who voluntarily participated in the interview process. All participants were 50 years and older, and living with HIV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants took part in a face-to-face, semi-structured interview [each approximately 60 min in length] between June and November 2021. There were sixteen [16] individuals who voluntarily participated in the interview process. All participants were 50 years and older, and living with HIV.…”
Section: Resultsmentioning
confidence: 99%
“…Physical activity and exercise can be used to improve overall function and quality of life in older populations living with HIV [ 16 ]. Physical activity and exercise participation also appear to be a safe and effective way to prevent the negative health outcomes associated with comorbidities in older people living with HIV [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chung et al [ 33 ] implemented an intervention of moderate-intensity aerobic and resistance exercise lasting 45 min twice a week, and Oursler et al [ 17 ] implemented an intervention of high-intensity aerobic exercise lasting 20–45 min three times a week. A previous scoping review reported that moderate-to-high intensity aerobic exercise and combined aerobic and resistance training were effective for enhancing the walking capacity of older adults living with HIV [ 41 ]. Therefore, we suggest that health care providers should consider providing physical activity interventions such as combined aerobic and resistance training or high-intensity aerobic exercise for improvement of walking capacity in older adults living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, increases in life expectancy among PWH are accompanied by challenges of both HIV and aging. While the majority of the literature on PWH focuses on younger samples, 4 older people living with HIV (OPWH) (aged ≥50 y of age) 5,6 are now facing unique challenges, thus shifting the focus from HIV-related chronic illnesses to noncommunicable, age-related diseases, such as cardiovascular disease (CVD). [7][8][9][10][11] Multiple factors have been attributed to the increased risk of CVD observed in OPWH, including HIV infection itself and increased rates of traditional risk factors, such as inflammation and physical inactivity.…”
mentioning
confidence: 99%
“…39,40 Though there are general PA guidelines for PWH (ie, ≥30 min•d −1 of moderate intensity PA on ≥3 d•wk −1 ), 41,42 no clear guidelines for PA exist that are appropriate for OPWH aged 50 years and older. 4 However, sedentary behavior, defined as any waking behavior in the sitting, lying, and reclining positions with an energy expenditure of ≤1.5 metabolic equivalents (METs), also plays a unique role in inflammatory and cardiovascular health. 43 Sitting time, a surrogate measure of sedentary behavior, is independently associated with CVD incidence and mortality, certain cancers, type 2 diabetes mellitus, and all-cause mortality.…”
mentioning
confidence: 99%